Serotonergic properties of the roots of Clerodendron capitatum - Abdelwahab, Siddig Ibrahim; Mohamed, Abdel Wahab Hassan; Mohamed, Osama Yousif; Elhassan Taha, Manal Mohamed; Abdul, Ahmad Bustamam; Al-Zubairi, Adel Sharaf (Science Publications, 2008)
The aim of this study is to investigate the pharmacological effects of the methanolic extract of Clerodendron capitatum, CC, (family verbenaceae). These investigations were carried out on isolated frog rectus abdominus muscle and rabbit aortic strips and jejunum and non-pregnant rat uterus pretreated with oestradiol. Results showed that CC did not demonstrate any contracting, relaxant or blocking effects on frog rectus abdominus muscle and rat aortic strip preparations. The extract produced a concentration-dependent (p<0.05, t-test, n = 6) decrease of the normal rhythmic contraction of rabbit jejunum, however, this effect was reversed by prior addition of cyproheptadine (non-specific 5-HT antagonist). In addition, CC also produced a stimulant activity on rat uterus which was blocked by cyproheptadine. Future study is recommended to study the specificity of CC to different 5-HT receptors by using different isolated animal tissues and specific 5-HT antagonists.